EVALUATION OF THE RALPH TYLER MODEL CURRICULUM IN THE MA'HAD AL-JAMIAH ARABIC LANGUAGE LEARNING PROGRAM AT UIN SYEKH ALI HASAN AHMAD ADDARY PADANGSIDIMPUAN - Irsal Amin Lubis; Rahmawati Rahmawati; Yasmadi Yasmadi (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
Evaluation of learning programs using various models can produce more accurate results. This study was conducted to explain the evaluation of Arabic language learning programs using the Ralph Tyler approach (design, implementation, and evaluation) in depth. This study is a descriptive qualitative study of curriculum texts and learning processes. To obtain data using interview techniques, observation, and document studies. The results of this study indicate that the design of Arabic language learning programs consists of three main aspects, namely program objectives, indicators, and target achievement of vocabulary that must be distributed. Program implementation includes implementation indicators, process implementation, teaching materials, learning methods, implementation of language sanctions, and additional activities. Program evaluation includes idea evaluation, design evaluation, implementation evaluation, and supporting factor evaluation. From the results of this study, it can be concluded that it is still more on the implementation aspect because the influence of culture is still very strong.